Kepemimpinan dalam Perspektif Islam - Muhammad Olifiansyah; Wahyu Hidayat; Bimansyah Putra Dianying; Muhammad Dzulfiqar (UIN Mataram, 2020)
A leader is someone who has a great responsibility in the organization for social life, being a leader must have a good relationship in cultural life so that it can be used as an example by its members. In Islam itself it is conveyed to the Ummah to become a leader in accordance with the existing Shari'a in the teachings of Islam, which subsequently leads to Islamic Leadership. Islamic leadership is a balance of leadership with the concept of the world and the hereafter, the task of leadership is not only a task that is held only for members, but also in the presence of Allah SWT. Allah has sent an Apostle who can be an example for Muslims to carry out Islamic Leadership as the Prophet Muhammad. Islamic leadership prioritizes the values ??put forward by Islam and also everything that is done because it expects God's blessing. Islamic leadership is more than part of the goals taken while in organizational leadership in general, support the strengthening of the establishment of Islamic order in the organization. Islamic leadership supports absolute leadership or leadership that is authorized, this leadership has a distinct characteristic of leadership in general.